Medial and lateral vestibulospinal projections to the cervical spinal cord of the squirrel monkey - Boyle, Richard (Frontiers in Neurology, 2025)
IntroductionThe brainstem vestibular nuclei neurons receive synaptic inputs from inner ear acceleration-sensing hair cells, cerebellar output neurons, and ascending signals from spinal proprioceptive-related neurons. The lateral (LVST) and medial (MVST) vestibulospinal (VS) tracts convey their coded signals to the spinal circuits to rapidly counter externally imposed perturbations to facilitate stability and provide a framework for self-generated head movements.MethodsThe present study describes the morphological characteristics of intraaxonally recorded and labeled VS neurons monosynaptically connected to the 8th nerve. The visualization of axon location in the descending medial longitudinal fasciculus (MLF) differentiated ipsi- (i) and contralateral (c)-projecting MVST neurons. Vestibuloocular collic (VOC) neurons were comparably typed as cMVST cells but were also antidromically activated from the rostral MLF. Cervical-only LVST neurons projected ipsilaterally in the lateral to ventrolateral funiculi. Targets of VS axons, such as central cervical nucleus neurons, sternocleidomastoid, trapezius, and splenius motoneurons, were identified using anti- and orthodromic electrical stimuli and intra-somatically labeled to describe their local spinal morphology.ResultsThirty-five VS neurons (26% of the 134 attempted samples) were successfully labeled to permit a moderate to (near) complete reconstruction of their trajectories and synaptic innervations. VOC neurons exhibited a prolific innervation of caudal brainstem nuclei, extensively innervated laminae VII and VIII, and, to a lesser extent, lateral and ventromedial lamina IX, from C1 to C8, and on average issued 15 branches along their trajectory with 92 terminal and en passant boutons per branch. The VOC innervation was either uniformly distributed among the cervical segments, indicating a more global control of head and neck movement, or restricted specific spinal segments, indicating a more precise motor control strategy. The innervation pattern of iMVST axons resembled that of VOC and cMVST axons but was less extensive and supplied mostly the upper two cervical segments. LVST and cMVST neurons exhibited a predominantly equally weighted innervation of separate and joint moto- and inter-neuronal spinal circuits along their cervical trajectory.DiscussionTheir extensive axon branching distribution in the ventral horn provides a redundant and variable synaptic input to spinal cell groups. This suggests a common and site-specific control of the head and neck reflexes.